EUS - Brugge, William R. (Endoscopy, 2013)
EUS has undergone a rapid change in the past few years as the technique has evolved from a primarily imaging modality with radial instruments to an interventional and therapeutic procedure using linear EUS instruments. Digestive Disease Week (DDW) 2013 presented a large number of excellent EUS abstracts. I have selected abstracts from around the world with a range of topics, but focusing on new therapies.